(untitled) (City: History, Culture, Society, 2022)
The paper investigated the history of the development of Nowa Huta the key achievement of the post-WWII urban planning and architecture in Kraków and Poland focusing on the rise of the Centre E Estate, the late 1980s part of the ensemble. The history of one housing complex helps to understand the reasons for the rise and development of postmodern aesthetics in the local architecture of Krakow during the last years of the domination of the communist regime.